Effect of Music Selection on Anxiety Level during Intravitreal Injections for Individuals of Varying Cultures. (3rd September 2022) - Brosh, Koby; Roditi, Eduardo; Wasser, Lauren M.; Aryan, Ahmad; Hanhart, Joel; Potter, Michael J.
ABSTRACT: Purpose: To investigate music selection as a treatment for anxiety during Intravitreal injections (IVI) for individuals of varying cultures. Methods: 106 individuals were enrolled in this randomized controlled study. Individuals were randomized into one to three categories: (1) a control group in which the IVI procedure was performed without music (n = 35), (2) an experimental group in which the music was selected by the physician (n = 36), (3) an experimental group in which the music was selected by the patient (n = 35). After the procedure, all patients responded to a questionnaire regarding their level of experienced anxiety, pain and discomfort (grade 0–10). The primary outcome was anxiety level during the procedure. Results: The experimental group in which patients selected music had higher number of patients with low anxiety score compared to the other groups (anxiety score <4 in 19, 18 and 27 patients, respectively, p = .04). Interestingly, patients who answered the questionnaire in Arabic were less likely to desire music on subsequent injections compared to Hebrew and English speakers (52% Vs 78% Vs 100%, p = .02). Music was deemed by both experimental groups as an effective method to induce relaxation (average score of 6.6 and 7.2 in group 2 and 3, respectively). Preference for music on subsequent injections was increased in both experimental groups compared to the control group ( P < .01). Patients in the third group preferred music selection on future injections more than the other groups ( P < .01). Conclusion: Music selection may be an effective way to reduce anxiety levels during IVI. Preference for music during future injections is higher in patients who were exposed to music during IVI and may be influenced by culture.